2018
DOI: 10.5194/acp-2018-516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Connecting regional aerosol emissions reductions to local and remote precipitation responses

Abstract: Abstract. The unintended climatic implications of aerosol and precursor emission reductions implemented to protect public health are poorly understood. We investigate the precipitation response to regional changes in aerosol emissions using three 15

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…Thus, NTCF mitigation generally increases precipitation in most world regions (although, in some regions, this is a smaller decrease) but the signal is less robust than that for surface temperature. Furthermore, in agreement with prior studies (Levy et al, 2013;Westervelt et al, 2017;Zhao et al, 2018;Westervelt et al, 2018;Scannell et al, submitted), precipitation increases in several monsoon regions, including east Africa, south Asia, and east Asia.…”
Section: Regional Climate and Air Quality Trendssupporting
confidence: 92%
“…Thus, NTCF mitigation generally increases precipitation in most world regions (although, in some regions, this is a smaller decrease) but the signal is less robust than that for surface temperature. Furthermore, in agreement with prior studies (Levy et al, 2013;Westervelt et al, 2017;Zhao et al, 2018;Westervelt et al, 2018;Scannell et al, submitted), precipitation increases in several monsoon regions, including east Africa, south Asia, and east Asia.…”
Section: Regional Climate and Air Quality Trendssupporting
confidence: 92%
“…The anticyclonic anomaly in the North Atlantic also causes Europe to be anomalously dry relative to 1979-1993, while the Mediterranean is anomalously wet (Figure 3(b)). This positive North-Atlantic-Oscillation-like response is consistent with the responses seen by Allen and Sherwood (2011) and Westervelt et al (2018) in response to increases in global aerosols. Note, however, that Westervelt et al (2018) identified a degree of model-sensitivity in the North Atlantic response to global aerosols, and identified an increase in Mediterranean precipitation that we do not see here.…”
Section: Resultssupporting
confidence: 84%
“…More recently, however, most of the SST variance over the Atlantic was found to be radiatively forced also in other models Murphy et al, 2017), with a distinct contribution of anthropogenic aerosols on both temporal and spatial variability. Note that aerosol impact on SSTs elsewhere, possibly including decadal El Niño-Southern Oscillation variability, has also been suggested (e.g., Sutton & Hodson, 2007;Westervelt et al, 2018).…”
Section: Geophysical Research Lettersmentioning
confidence: 97%